Treatment of Periprosthetic Joint Infection and Fracture-Related Infection With a Temporary Arthrodesis Made by PMMA-Coated Intramedullary Nails – Evaluation of Technique and Quality of Life in Implant-Free Interval - Walter, Nike; Baertl, Susanne; Lang, Siegmund; Szymski, Dominik; Weber, Johannes; Alt, Volker; Rupp, Markus (Frontiers in Surgery, 2022)
Background: Antimicrobial coating of intramedullary nails with polymethyl methacrylate (PMMA) bone cement promises infection control and stabilization for subsequent bone healing. However, when removing the implant bone cement can debond, and remain in the medullary cavity of the long bones representing a nidus for reinfection. This work presents a technique comprising reinforcement of PMMA-coated intramedullary nails with cerclage wire to prevent such problems in patients treated for fracture-related infection (FRI) or knee periprosthetic joint infection (PJI) with a static spacer as temporary arthrodesis allowing weight-bearing in the implant free interval. Outcomes of this surgical treatment were evaluated in terms of (i) associated complications and (ii) patient-reported quality of life. Methods: In this retrospective case series twenty patients with PJI (n=14, 70%) and FRI (n=6, 30%) treated with a PMMA-coated intramedullary nails reinforced with cerclage wire between January 2021 to July 2021 were included. Quality of life during the implant free interval was evaluated with the EQ-5D, the SF-36 and an ICD-10 based psychological symptom rating and compared to previously analysed cohorts of successfully treated PJI and FRI patients with achieved eradication of infection and stable bone consolidation. Results: Complications during the implant free interval comprised a broken nail in one case (5.0%) and a reinfection in one case (5.0%). Coating specific side effects and cement debonding during removal did not occur. The mean physical health component score (PCS) of the SF-36 was 26.1± 7.6, and the mean mental health component score (MCS) reached a value of 47.1± 18.6. The mean EQ-5D index value was 0.36± 0.32 and the mean EQ-5D VAS rating 47.4± 19.4. The scores were significantly lower in comparison to the successfully treated FRI cohort, but not the PJI cohort. The mean ISR scores revealed psychological symptom burden on the depression scale and enhanced levels of anxiety in comparison to healed FRI and PJI patients. Conclusion: Reinforcement of PMMA (polymethyl methacrylate) bone cement-coated implants seems a reasonable treatment option to create a temporary arthrodesis preventing detachment of the bone cement when the implant is removed. Level of Evidence: IV